2014
DOI: 10.1016/j.jpain.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Involvement in Chronic Musculoskeletal Pain

Abstract: There is emerging evidence that chronic musculoskeletal pain is associated with anatomical and functional abnormalities in gray matter. However, little research has investigated the relationship between chronic musculoskeletal pain and white matter (WM). In this study, we used whole-brain tract-based spatial statistics, and region-of-interest analyses of diffusion tensor imaging (DTI) data to demonstrate that patients with chronic musculoskeletal pain exhibit several abnormal WM integrity as compared to health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 75 publications
6
64
1
1
Order By: Relevance
“…Symbols are scaled to age to demonstrate the independent nature of these findings. The partial correlation coefficient between FA, MD and radial diffusivity values and BDI is −0.6279, 0.6092 and 0.6177, respectively (p<0.05, adjusted for age and gender) studies have reported that increased axial diffusivity was associated with chronic pain or hyperalgeria [18,19]. This voxel-based regional change in the present study is the confirmatory finding that supports a previous ROI study that also showed a difference in DTI values in the auditory cortices of tinnitus patients compared with normal control subjects [6].…”
Section: Discussionmentioning
confidence: 96%
“…Symbols are scaled to age to demonstrate the independent nature of these findings. The partial correlation coefficient between FA, MD and radial diffusivity values and BDI is −0.6279, 0.6092 and 0.6177, respectively (p<0.05, adjusted for age and gender) studies have reported that increased axial diffusivity was associated with chronic pain or hyperalgeria [18,19]. This voxel-based regional change in the present study is the confirmatory finding that supports a previous ROI study that also showed a difference in DTI values in the auditory cortices of tinnitus patients compared with normal control subjects [6].…”
Section: Discussionmentioning
confidence: 96%
“…The tapetum is the temporal component of the corpus callosum (Mori et al, ) formed by decussating fibers in the splenium that arch over the atrium of the lateral ventricle and course inferiorly in the posterior and temporal horns of this ventricle (Sarikcioglu et al, ). In contrast, more evidence exists for WM deficits in the corpus callosum (genu, rostrum, body, splenium, tapetum) in chronic musculoskeletal pain patients (Lieberman et al, ) and mild TBI patients (Xiong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Association fibers, namely (6) the cingulum cingulate gyrus (i.e., subgenual and retrosplenial part of the cingulum) and (7) the cingulum hippocampus (i.e., parahippocampal part of the cingulum) (Lieberman et al, ; Mori et al, ) and (8) fornix and stria terminalis (Borsook et al, ; Chen et al, ; Upadhyay et al, ). Finally, commissural fibers, that is (9) the tapetum of the corpus callosum (Kim et al, ; McAllister, ) and (10) the splenium of the corpus callosum (Lieberman et al, ). Acceleration–deceleration of the brain is believed to affect the superior cerebellar peduncles, and periventricular WM (McAllister, ), for example, tapetum of the corpus callosum (Kim et al, ; Sarikcioglu et al, ; Todd & Lempert, ).…”
Section: Methodsmentioning
confidence: 99%
“…The inferior fronto-occipital fasciculus links cortical regions involved in the processing of pain, emotion, and rewards27. Diffusion alterations in the uncinate fasciculus have been correlated with pain experience and perception28. Microstructural alterations of the anterior thalamic radiation and cingulated gyrus connect cortical regions also involved in body perception.…”
Section: Discussionmentioning
confidence: 99%